(untitled) (Journal of the College of Basic Education, 2026)
The research aimed to determine the extent to which the Biology textbooks for the first and second intermediate grades incorporate critical thinking skills. To achieve this objective, the researchers used the descriptive analytical method, specifically the content analysis method. The content of the textbooks was analyzed using a content analysis tool that was constructed based on critical thinking skills in its preliminary form. This tool included a list of critical thinking skills, represented by (31) sub-indicators distributed across (5) main skills: the Interpretation Skill (7 indicators), the Deduction Skill (6 indicators), the Inference Skill (5 indicators), the Hypothesizing Skill (7 indicators), and the Argument Evaluation Skill (6 indicators). After presenting the tool to a arbitrators and experts, the tool remained the same, with minor modifications. The researchers used frequencies, percentages, and Holsti’s coefficient formula to find the reliability coefficient as statistical ways. The research concluded that the critical thinking skills that should be available in the Biology textbooks for the intermediate first and second grades consist of five main skills: the Interpretation Skill, the Deduction Skill, the Inference Skill, the Hypothesizing Skill, and the Argument Evaluation Skill. The availability percentages of critical thinking skills varied between the two textbooks. The Skill Interpretation was the most highly available skill among the critical thinking skills, followed by the Hypothesizing Skill in the second rank, then the Argument Evaluation Skill in the third rank, the Deduction Skill came in the fourth rank, and the Inference Skill was in the last rank. In view of results, the researchers recommend utilizing the results of research to develop Biology textbooks for the intermediate stage in the Republic of Iraq in light of critical thinking skills. They also recommend revisiting the content of Biology textbooks for all educational stages in terms of their coverage of critical thinking skills, because of their importance in building the learner’s critical personality, achieving belonging and citizenship, and confirming their readiness for success in various areas of life.